Contribution of HLA-B*51:01 and -A*26:01 to Behçet's disease and their clinical association in Thai patients - Worawit Louthrenoo (2020)
© 2020 Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd Aims: To investigate susceptible human leukocyte antigen (HLA) alleles and their associations with clinical features in Thai patients with Behçet's disease (BD). Method: Eighteen HLA-A and 36 HLA-B alleles were determined in 42 Thai BD patients and 99 healthy controls (HCs) by reverse line blot assay, and reconfirmed by MICRO SSP assay. Results: The BD patients had significantly higher allele frequency (AF) of HLA-B*51 than the HCs (13.10% vs 5.05%, P =.025). The AF of HLA-A*26, -A*26:01 and -B*51:01 also was higher and almost reached statistical significance (5.59% vs 1.52%, P =.054, 5.95% vs 1.52%, P =.054 and 10.71% vs 4.04%, P =.051, respectively). However, the BD patients had significantly higher AF of either HLA-A*26:01 or -B*51:01 (16.67% vs 5.56%, P =.005), or -A*26:01 or -B*51X (19.05% vs 6.56%, P =.003). The AF of HLA-B*51:01 and -B*51X increased significantly in -A*26:01 non-carrier BD patients (12.16% vs 4.17%, P =.024 and 14.86% vs 5.21%, P =.019, respectively); and that of HLA-A*26:01 was significantly higher in -B*51X non-carrier BD patients (7.58% vs 1.67%, P =.034). HLA-B*51:01 associated significantly with the presence of posterior uveitis and visual impairment (18.18% vs 2.50%, P =.031 for both conditions). HLA-B*51:01 was not observed in BD patients with gastrointestinal involvement or arthritis. Furthermore, the AF of HLA-B*51:01 was significantly higher in HLA-A*26:01 non-carrier BD patients without arthritis (17.30% vs 0%, P =.050). Conclusion: HLA-B*51:01 was a susceptible allele for Thai BD patients, and associated with posterior uveitis and visual impairment. HLA-A*26:01 was another susceptible allele in HLA-B*51X non-carrier patients. The protective effect of HLA-B*51:01 on arthritis needs further investigation.